Genesis of the Essential Content of the Hotel Service as an Object of Consumer-Oriented Marketing - Khayrullaeva Nilufarbeim Nematilloyevna; Narzullayeva Gulchekhra Salimovna; Tairova Masuma Muxammedovna (International Journal on Economics, Finance and Sustainable Development, 2021)
In the article development of theoretical foundations and methodological provisions for the formation of an integrated approach to the development of a marketing strategy for hotel services, the use of marketing mix tools to ensure the effectiveness of marketing communications with hotel consumers services.